Technical report: the study of growth rate of mangrove by comparing between Blackman’s equation and the real GDP unadjusted year-on-year quarterly growth formula / Naqiuddin Fadlysham, Mohammad Hafiz Mansor and Tengku Zul Safwan Tengku Izham - Fadlysham, Naqiuddin; Mansor, Mohammad Hafiz; Tengku Izham, Tengku Zul Safwan (2016)
Mangroves are fundamental to sustain coastal environments hale and hearty, to offer nutrients for a number of food chains, and to contribute priceless goods and services that maintain and expand human livelihoods. Mangroves act as natural barriers for unwanted events caused by the seas. Sea-level reconstruction offers protection from waves, tidal bores, tsunamis and shoreline erosion as to provide stability for environmental constancy. Mitigation of effects by climate change, provision nutrients for marine life, prevention soil erosion, these occurrences can be done by plantation of mangroves. Blackman's equation is one of the sources in calculating growth rate of any plants and was published by R.B. Blackman in 1943. Inputs needed in generating this equation are various, for example weight of plants, surface area of leaves, density of plants and mass of leaves. Regardless formulas used in getting growth rate of plants either exponential growth equation or growth rate formula, still Blackman's gives same outputs. This means Blackman's can be exposed to students as another way to solve questions related to find growth rate of plants. However, re-planting of mangroves may help to reduce huge impacts of any unexpected phenomenal mother-nature's events nearby seas.